Estudo da resistência à corrosão do aço inoxidável duplex UNS S31803 ou SAF 2205 submetido a processo de soldagem - Amaro, Lucinda Oliveira (2006)
The aim of this work is to study the influence of the welding energy in the corrosion resistance of UNS S31803 or SAF 2205, duplex stainless steel. For this purpose, double loop electrochemical potentiokinetic reactivation and cyclic polarization were the electrochemicaltechniques used to evaluate the susceptibility of the welded steel to intergranular and pitting corrosion, respectively. The microstructure observed using an optical microscope wich also made possible to assess the phase quantification. Hardness measurements were also carried out. The electrochemical results showed that the welded steel is not susceptible to the intergranular. On the other hand, all the welded steel were susceptibles to pitting corrosion wich is rising with the welding energy. Aditionally, the pitting potencial increase with the ferrite content in the welded steel, while the hardness is not strongly influenced by the welding energy